Black swan: bibliometric analysis and development of research agenda. Issue 7 (20th January 2021) - Parameswar, Nakul; Chaubey, Akriti; Dhir, Sanjay
Abstract : Purpose: There has been an increasing interest amongst the researchers to work and explore, "Black Swan" events which are not well studied. However, the "Black Swan" events hold an eminent relevance amongst academicians and practitioners. The present study offers nuanced understanding of "Black Swan" events. Design/methodology/approach: We undertook an extensive bibliometric analysis of the extant literature using "Black Swan" as guiding keyword with the help of SCOPUS database. Findings: The search for articles only yielded 59 articles. Our analyses highlight the prominent works, authors and journals. Further, this study reveal the research gaps that may help guide future scholars interested in "Black Swan" events to examine in different context. Research limitations/implications: The current study develops a research agenda and offers numerous research directions. Research on "Black Swan" events can be apprehended at three different stages – pre-black swan event, about black swan event and post-black swan event with identified sub-themes. Originality/value: This paper is the pioneer research work to dedicatedly analyse the existing set of literature with "Black Swan".